Far-field unlabeled super-resolution imaging with superoscillatory illumination - Rogers, Edward T. F. (2020)
Unlabeled super-resolution is the next grand challenge in imaging. Stimulated emission depletion and single-molecule microscopies have revolutionized the life sciences but are still limited by the need for reporters (labels) embedded within the sample. While the Veselago–Pendry “super-lens,” using a negative-index metamaterial, is a promising idea for imaging beyond the diffraction limit, there are substantial technological challenges to its realization. Another route to far-field subwavelength focusing is using optical superoscillations: engineered interference of multiple coherent waves creating an, in principle, arbitrarily small hotspot. Here, we demonstrate microscopy with superoscillatory illumination of the object and describe its underlying principles. We show that far-field images taken with superoscillatory illumination are themselves superoscillatory and, hence, can reveal fine structural details of the object that are lost in conventional far-field imaging. We show that the resolution of a superoscillatory microscope is determined by the size of the hotspot, rather than the bandwidth of the optical instrument. We demonstrate high-frame-rate polarization-contrast imaging of unmodified living cells with a resolution significantly exceeding that achievable with conventional instruments. This non-algorithmic, low-phototoxicity imaging technology is a powerful tool both for biological research and for super-resolution imaging of samples that do not allow labeling, such as the interior of silicon chips.